Ensuring Competitive Advantage and Managing Risks in The Hotel Business - Eldor Makhmudov (Periodica Journal, 2024)
The article explores how The Oasis, a leading hotel, is transforming hospitality by integrating advanced technology into its operations. It highlights the seamless incorporation of virtual concierge services, artificial intelligence, and IoT devices to enhance guest experiences. Despite the emphasis on technology, the article emphasizes the continued importance of personalized service and human interaction. Additionally, The Oasis is committed to sustainability and social responsibility, further distinguishing it in the hospitality industry.
Keywords: Hospitality; Digital Age; Technology Integration